2019
DOI: 10.6061/clinics/2019/e1147
|View full text |Cite
|
Sign up to set email alerts
|

Who and Where are the University of São Paulo Medical School Graduates?

Abstract: OBJECTIVE:To evaluate the impact of a complex-care-based medical school in the context of the Brazilian health care system on students' career choices.METHODS:This was a retrospective cross-sectional study based on medical regulatory organization records. It included records for 7,419 physicians who graduated from FMUSP. Geographic data were analyzed using Kernel maps, and the statistical analysis was performed with SPSS® version 24.0. A p-value less than 0.05 was considered significant.RESULTS:Of the 7,419 ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 14 publications
0
6
1
8
Order By: Relevance
“…In the topic of feminization, it was found that there are differences between genders when comparing the groups of FMUSP and non-FMUSP alumni in the residency. The percentage of women in the group of FMUSP alumni (40.7%) was higher than the frequency of 31.4% found in the study by Gameiro et al 13 , which assessed the demographics of doctors trained by this institution between the years 1940 and 2013. The period covered in the present study, 1999 to 2019, may help explaining this difference.…”
Section: Discussioncontrasting
confidence: 64%
See 4 more Smart Citations
“…In the topic of feminization, it was found that there are differences between genders when comparing the groups of FMUSP and non-FMUSP alumni in the residency. The percentage of women in the group of FMUSP alumni (40.7%) was higher than the frequency of 31.4% found in the study by Gameiro et al 13 , which assessed the demographics of doctors trained by this institution between the years 1940 and 2013. The period covered in the present study, 1999 to 2019, may help explaining this difference.…”
Section: Discussioncontrasting
confidence: 64%
“…It was the most popular program among these residents, which contradicts the national trend, in which General Surgery is in 3rd place among the most frequent specialties in Brazil 7 . This may be due to FMUSP's strong history of training surgeons, as pointed out in previous studies, which reported that, over 74 years, the most frequent specialty of FMUSP graduates was Surgery, with a total of 826 surgeons in the period evaluated (more than 10% of all graduates who specialize) 13 .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations